Akselerasi Ekosistem Pariwisata Halal Global : Peran Strategis Bank Syariah dalam Pembiayaan Infrastruktur dan Integrasi Digital - Taufikur Rahman; Sunarsih Sunarsih (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2026)
Global halal tourism is growing rapidly but is hindered by limited infrastructure and constrained access to Sharia financing. This study analyzes the strategic role of Islamic banks as financiers and digital integration innovators within the halal tourism ecosystem. Using a descriptive-qualitative literature research method, the study reveals three main findings. First, Islamic banks play a dual role as funding providers (via musyarakah and mudharabah) and ecosystem developers. Second, digitalization via AI and blockchain is a key catalyst for operational efficiency and end-to-end service integration. Third, integrating Islamic finance and tourism through digital platforms strengthens the competitiveness of global halal destinations. In conclusion, accelerating this ecosystem requires cross-sectoral collaboration supported by financing innovations and digitalization.